2009
DOI: 10.1002/nau.20704
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of bladder diary with urinary perception to assess overactive bladder symptoms in community‐dwelling women

Abstract: A bladder diary that includes a new bladder perception grade was thought to be useful in assessing urinary sensation or incontinence as well as voiding pattern. The causes of symptoms such as urgency or urinary frequency may be different between the Normal, OAB-Dry, and OAB-Wet groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 15 publications
3
6
0
Order By: Relevance
“…The average voided volume in this study (322.6 ml AE SD137) is similar to the average maximum voided volumes on the bladder diary in the study by Honjo et al 29 They reported that women with OAB_dry and OAB_wet had average maximum voided volumes of 438.6 ml (SD ¼ 124.1) and 395.5 ml (SD ¼ 78.9), respectively, while their average voided volumes were 228.9 ml (SD ¼ 63.4) and 208.8 ml (SD ¼ 67.5), respectively. 29 Therefore, it is possible that the women in this current study were overfilled during testing and this factor played a role in their voiding parameters. Thus, the values of voiding parameters with cystometric bladder capacity may be different to those with naturally voided volumes and more research is needed on this difference.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The average voided volume in this study (322.6 ml AE SD137) is similar to the average maximum voided volumes on the bladder diary in the study by Honjo et al 29 They reported that women with OAB_dry and OAB_wet had average maximum voided volumes of 438.6 ml (SD ¼ 124.1) and 395.5 ml (SD ¼ 78.9), respectively, while their average voided volumes were 228.9 ml (SD ¼ 63.4) and 208.8 ml (SD ¼ 67.5), respectively. 29 Therefore, it is possible that the women in this current study were overfilled during testing and this factor played a role in their voiding parameters. Thus, the values of voiding parameters with cystometric bladder capacity may be different to those with naturally voided volumes and more research is needed on this difference.…”
Section: Discussionsupporting
confidence: 89%
“…The women in the current study had permission to void when they reached the cystometric bladder capacity during a pressure‐flow study. The average voided volume in this study (322.6 ml ± SD137) is similar to the average maximum voided volumes on the bladder diary in the study by Honjo et al They reported that women with OAB_dry and OAB_wet had average maximum voided volumes of 438.6 ml (SD = 124.1) and 395.5 ml (SD = 78.9), respectively, while their average voided volumes were 228.9 ml (SD = 63.4) and 208.8 ml (SD = 67.5), respectively . Therefore, it is possible that the women in this current study were overfilled during testing and this factor played a role in their voiding parameters.…”
Section: Discussionsupporting
confidence: 86%
“…Fewer than two voids each night may cause no major problem, while two or more give rise to impaired quality of life due to sleep disturbance . There is increasing evidence that a bladder diary with a self‐reported grading of urinary perception or urgency scale can be a clinically powerful tool for patient self‐assessment of urinary sensory function, especially when the bladder diary can provide not only the voided volumes but also the degree of urgency perception at every single void . Since OAB is diagnosed by symptoms alone, its assessment is very important for physicians.…”
Section: Introductionmentioning
confidence: 99%
“…Later, their comparison of SR-BDs with filling cystometry demonstrated that sensation-related symptoms are more accurately studied by the use of SR-BDs compared to cystometry [14]. Subsequently, the use of a 3-day SR-BD was assessed in the analysis of overactive bladder symptoms in community-dwelling women [15] and to evaluate differences between urinary-incontinent and continent women [16]. Both showed that patients with OAB void with lower volumes and higher urgency compared to healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%